2017
DOI: 10.1007/s41779-017-0155-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electrical conductivity and dielectric relaxation behavior of LiHf2(PO4)3 ceramic powders

Abstract: Lithium hafnium phosphate LiHf2(PO4)3 (LHP) was synthesized via solid-state synthesis technique. The sintering behavior, structure, and phase composition of the as-prepared sample was analyzed using X-ray diffraction (XRD) characterization technique. The XRD-Rietveld refinement analysis showed that after sintering at low temperatures 500 to 1000 °C, it exhibited various secondary phases. However, a single phase was observed as the sintering temperature increases from 1100 to 1200 °C. LHP sintered at 1100 °C pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 25 publications
4
5
0
Order By: Relevance
“…From this data, it was understood that there was a proportional relationship between average crystallite size and microstrain. This type of observation was also found in the literature [20][21][22][23][24][25][26]. The lattice constants were evaluated and presented in table 1.…”
Section: Introductionsupporting
confidence: 80%
“…From this data, it was understood that there was a proportional relationship between average crystallite size and microstrain. This type of observation was also found in the literature [20][21][22][23][24][25][26]. The lattice constants were evaluated and presented in table 1.…”
Section: Introductionsupporting
confidence: 80%
“…2. The XRD results of unsubstituted LHP shows the sample powder sintered at 1100 °C for 3 h exhibited single phase with no secondary phases as reported elsewhere [16]. The unit cell volume and lattice parameters of the LHP analyzed are shown in Table 2 and the parameters are found to be in close agreement with the data reported by Chang et al [17,18] where a = b = 8.8285 Å, c = 22.0190 Å and V = 1484.40 Å 3 .…”
Section: Tga/dtg Analysissupporting
confidence: 85%
“…The presence of space charge also contributes to the increase in the conductivity. It is also observed that the un-substituted LHP pellet showed low AC conductivity in the order of 2.45 × 10 −4 Ω −1 m −1 at room temperature as reported elsewhere [16]. On the other hand, the Al substituted sintered pellets exhibited high Li ionic conductivity than the un-substituted LHP.…”
Section: Ionic Conductivitysupporting
confidence: 80%
“…4 as a shoulder on the right-hand side of the horizontal axis, has been calculated as 2.5 µs. When the arrangement of relaxation times is considered, the relaxation times of the order of ms and µs can be attributed to dipolar [23] and ionic polarizations [24], respectively. The sizes of semicircles become smaller with increasing Bi content.…”
Section: Resultsmentioning
confidence: 99%